Formation of lateral chemical gradients in plasma polymer films shielded by an inclined mask. Issue 4 (23rd February 2018) - Vandenbossche, Marianne; Petit, Laurène; Mathon‐Lagresle, Julie; Spano, Fabrizio; Rupper, Patrick; Bernard, Laetitia; Hegemann, Dirk
Abstract : Low pressure plasma deposition conditions are investigated yielding oxygen‐containing lateral gradient coatings (aC:H:O) by means of an inclined static mask partly shielding the substrate. Such lateral gradient coatings are formed by the diffusion of film‐forming species with different reactivities underneath the mask. Surface characterization revealed varying film growth conditions below the mask different from direct plasma exposure with increasing distance from the mask/plasma edge: i) exponentially decreasing film growth; ii) decreasing roughness following the thickness trend; iii) decreasing hydrophilicity; iv) variation in cross‐linking; and v) different chemical composition. Oxygen‐rich film‐forming species appeared to react closer to the mask/plasma edge, while oxygen‐poor film‐forming species can diffuse deeper, leading to a pronounced gradient in chemical composition and in cross‐linking in the masked area. Abstract : Chemical and structural analyses of aC:H:O lateral gradient coatings showed three main areas: 1) the unmasked area, with [O]PPF /[C]PPF ∼19%; 2) the first 1 cm below the mask close to the mask/plasma edge with [O]PPF /[C]PPF ∼26%; and 3) the fully masked area, with [O]PPF /[C]PPF ∼13%. This result highlights the diffusion of the O‐containing film‐forming species below the mask, and their separation over the surface due to their different sticking probabilities.